Robust Bidirectional Platoon Control for Mesh Stability of Vehicular Systems With Uncertain Kinematics and Dynamics - Boo, Junseok; Chwa, Dongkyoung (IEEE Transactions on Intelligent Vehicles, 2024)
This study introduces an adaptive integral sliding mode disturbance observer (AISMDOB)-based robust bidirectional platoon control method, aiming to ensure mesh stability in vehicular systems. Most existing platoon control studies only focus on error propagation stability in either the longitudinal or lateral direction, neglecting the uncertainties in kinematics and dynamics of vehicular systems. The study proposes new coupled spacing error dynamics derived from vehicle kinematics and extended look-ahead-based coupled spacing errors to ensure both the longitudinal and lateral error propagation stability (that is, mesh stability) and are subsequently utilized to develop the novel AISMDOB, which improves the existing integral sliding mode disturbance observers (ISMDOBs) by incorporating adaptive estimation of unknown disturbance bounds while preserving their advantages. The AISMDOB-based platoon control method is then proposed using both robust kinematic and dynamic controllers to effectively compensate for the kinematic disturbances and dynamic model uncertainties, thereby reducing chattering phenomenon and ensuring the asymptotic convergence of spacing and velocity errors. Additionally, the proposed method can prevent cutting-corner behaviors during cornering maneuvers by utilizing the coupled spacing error dynamics. Simulation and experimental results verify the effectiveness of the proposed method through comparison with ISMDOB-based, sliding mode control (SMC)-based, and previous extended look-ahead-based methods.
Keywords: Adaptive integral sliding mode disturbance observer; Bidirectional platoon control; Coupled spacing error dynamic; Cutting corners; Cutting-corner behavior; Disturbance observer; Error dynamics; Integral sliding mode; Kinematics and dynamics; Mesh stabilities; Platoon controls; Spacing errors; Uncertain dynamics; Uncertain kinematics; Vehicular system with uncertain kinematic and dynamic; Vehicular systems; Adaptive integral sliding mode disturbance observer (AISMDOB); bidirectional platoon control; coupled spacing error dynamics; cutting-corner behavior; mesh stability; vehicular systems with uncertain kinematics and dynamics